Respostas
respondido por:
57
a-)
x 3
3 = 3 => x = 3
==============================
b-)
x 3 -x 3
(1/5) = 5 => 5 = 5 => -x = 3 => x = - 3
==========================================
c-)
x 1/2 2x 5/2
4 = 32 => 2 = 2 => 2x = 5/2 => x = 5/4
===========================================
x 3
3 = 3 => x = 3
==============================
b-)
x 3 -x 3
(1/5) = 5 => 5 = 5 => -x = 3 => x = - 3
==========================================
c-)
x 1/2 2x 5/2
4 = 32 => 2 = 2 => 2x = 5/2 => x = 5/4
===========================================
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás